Filomeno V. Aguilar Jr. (2009). Maalwang Buhay: Family, overseas migration, and cultures of relatedness in Barangay Paraiso. [With J. E. Z. Peñalosa, T. B. T. Liwanag, R. S.Cruz I, and J. M. Melendrez]. Q.C.: Ateneo de Manila Univ. Press. 450 pages. - Tadeo, Joy Raquel R. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 6 No 1 (2010), 2010)
None